Factors Influencing the Level of Knowledge of Reproductive Age Women about Visual Inspection with Acetic Acid (VIA Test) at PMB S. April - May Period in 2023 - Sartika, Dewi Sartika; Sarimalini, Masayu Delta; Widiyanti, Wiwi (International Journal of Midwifery and Health Sciences, 2023)
Background: Cervical cancer is a disease caused by sexually acquired infection with Human Papiloma Virus (HPV) sub-types, especially sub-types 16 and 18 (WHO, 2016). IVA is an examination of the cervix (cervix) by looking directly (naked) at the cervix after wiping the cervix with a 3-5% acetic acid solution. Based on data from the Indonesian cancer foundation, in Indonesia 1 hour 1 person dies from cervical cancer and 34.4 per cent of cancers in women. The number of new cases of cervical cancer is 40 to 45 per day. Purpose: To find out what factors influence the level of knowledge of WUS on knowledge about VIA test in PMB S period April-May 2023? Methods: The design used was a survey with a "Cross Sectional" approach, namely research on several populations observed at the same time, The population taken in this study were all Women of Fertile Age (WUS) who conducted family planning at PMB S on 18 April - 08 May Tangerang Banten Year 2023 Results: Based on statistical tests, it was found that there was no significant relationship between age and the level of knowledge of women of childbearing age about visual inspection of acetic acid (VIA) test where the p value = 0.171 (p> 0.050), there was no significant relationship between education and the level of knowledge of women of childbearing age about visual inspection of acetic acid (VIA) where the p value = 0.196 (p> 0.050), it was found that there was no significant relationship between education and the level of knowledge of women of childbearing age about visual inspection of acetic acid (VIA) where the p value = 0.196 (p> 0.050).0.050), it was found that there was a significant relationship between work and the level of knowledge of women of childbearing age about visual inspection of acetic acid (VIA) test at PMB Siti Rahayu Kreo Tangerang Banten in 2023 where the p value = 0.012 (p> 0.050). Conclusion: There is no significant relationship between the level of knowledge of WUS and work, level of knowledge, age of WUS about visual inspection of acetic acid (VIA).